2003
DOI: 10.1016/s0042-6822(03)00375-1
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage leads to expansion of bacteriophage P4 procapsids in vitro

Abstract: Proteolytic cleavage of the structural proteins is an important part of the maturation process for most bacteriophages and other viruses. In the double-stranded DNA bacteriophages this cleavage is associated with DNA packaging, capsid expansion, and scaffold removal. To understand the role of protein cleavage in the expansion of bacteriophages P2 and P4, we have experimentally cleaved P4 procapsids produced by overexpression of the capsid and scaffolding proteins. The cleavage leads to particle expansion and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
3
1
Order By: Relevance
“…Presumably, the majority of the procapsids isolated from wild-type phage lysates represents a mature form of the procapsids, ready for DNA packaging and capsid expansion. We previously found that P4 procapsids could be artificially expanded by cleavage of gpN by trypsin (Wang et al, 2003). In contrast, the present results suggest that protein cleavage and capsid maturation and expansion are disconnected processes in vivo.…”
Section: Biochemical Characterization Of P2 and P4 Capsidscontrasting
confidence: 91%
“…Presumably, the majority of the procapsids isolated from wild-type phage lysates represents a mature form of the procapsids, ready for DNA packaging and capsid expansion. We previously found that P4 procapsids could be artificially expanded by cleavage of gpN by trypsin (Wang et al, 2003). In contrast, the present results suggest that protein cleavage and capsid maturation and expansion are disconnected processes in vivo.…”
Section: Biochemical Characterization Of P2 and P4 Capsidscontrasting
confidence: 91%
“…In the presence of both gpO and Sid, Sid takes precedence, leading to the formation of T =4 capsids (Wang et al, 2006). Consistent with this observation, gpO interacts only transiently with gpN, while Sid is stably associated with the procapsids until expansion occurs (Wang et al, 2003; Chang et al, 2008). …”
Section: Discussionsupporting
confidence: 66%
“…Alternatively, cleavage might destabilize intersubunit interactions in preparation for expansion. Indeed, experimental removal of the N-terminal 29 residues by trypsin treatment was previously shown to cause spontaneous capsid expansion of P4 procapsid shells (Wang et al, 2003). The presence of gpO might play a role in delaying the expansion until DNA packaging occurs [the P4 procapsids that were expanded in vitro (Wang et al, 2003) did not contain gpO].…”
Section: Discussionmentioning
confidence: 99%
“…Maturation was first documented by EM in 1976 using T4 polyheads (Laemmli et al, 1976), and since then it has been described at various resolutions in a number of other dsDNA bacteriophage (Conway et al, 2001; Dokland and Murialdo, 1993; Gan et al, 2006; Jiang et al, 2003; Wang et al, 2003). Regardless of the phage analyzed, there are common structural differences between pro phage capsids and mature capsids.…”
Section: Resultsmentioning
confidence: 99%